Teaching Internship Program for the Development of Student Teachers’ Pedagogical Competence: Students’ Voices - Irani Manasikana; Hartono Hartono (Universitas Islam Sultan Agung, 2021)
This study investigated English Education student teachers’ voices about teaching internship programs to develop their pedagogical competence. The study involved 29 English student teachers of an English Education study program who were selected purposively after they completed their internship programs. A mixed-method research design was adopted, and data were collected by a questionnaire and interviews. The finding suggests that the internship program helped them develop their pedagogical competence. The mean score of the questionnaire to measure their perception of the benefit of the internship program was 64.21, which belongs to the high category. Eighteen (18) respondents (62.07%) perceived that the program highly developed their pedagogical competence and the rest (37.93) perceived it moderately did. No respondent perceived that it had a low effect on the development of their pedagogical competence. The qualitative data also suggest that the student teachers could positively benefit from the internship program in terms of their improved understanding of students’ strengths and weaknesses, their understanding of curriculum and syllabus, teaching media, and teaching strategy to improve the learning process. With all the positive effects, a teaching internship program can be a tangible facility to improve pedagogical competence.